Analysis of Talent Management Implementation at the Domestic Policy Strategy Agency and the Ministry of Home Affairs - Gogo Ricky Martin Purba; Sampara Lukman; Karno, Karno (Sean Institute, 2025)
Talent management is basically a model of HR development based on talent. The implementation of talent management at BSKDN, especially UKE-1 Kemendagri, is still faced with several problems. This study aims to determine and analyze the implementation of talent management, obstacles and efforts to improve talent management in supporting the performance of BSKDN Kemendagri (UKE-I). This study was conducted with a qualitative approach that is descriptive in nature with a post-positivist approach design, namely a modification of the positivist approach. The informants in this study numbered 7 people. The results of the study concluded, namely: (1) Analysis of Efforts to Implement Talent Management at BSKDN and Kemendagri still requires improvement. Placement of HR is still not fully in accordance with the principles of optimal talent management. Many HR cannot channel their talents completely because they do not match the job formation they hold, because they are influenced by the procurement of job formation needs that limit employees in showing their talents. (2) Analysis of Inhibiting Factors in the Implementation of Talent Management at BSKDN and Kemendagri, including there is still coercion in the placement of HR that does not match the competencies they have and in the procurement of formations it is sometimes forced and the job formations that are opened do not always match the needs of the work unit. (3) Efforts that need to be made to support the Implementation of Talent Management at the BSKDN Ministry of Home Affairs are to make improvements through the realization of Smart ASN by building employee character that upholds integrity, works professionally, has a spirit of nationalism, and has a global perspective.